(untitled) (International Journal of Food and Nutritional Sciences, 2021)
By correctly positioning distributed generators (DG) in the optimum place, power quality and dependability of distributed power can be achieved. The integration of distributed generation was primarily increasing the necessity of optimization tools.This essay offers several reviews of current optimization methods that have been applied to DG unit problem-solving and sizing over the years. In contrast, this study examines the constantly expanding interest in the integration of distributed generation by overcoming all of the economic, technological, environmental, etc. Renewable Energy Sources (RES) are inexhaustible, clean, and free from pollution so they are considered widely rather than fossil fuels in distributed generation